2017
DOI: 10.3892/etm.2017.5148
|View full text |Cite
|
Sign up to set email alerts
|

ANXA1 affects cell proliferation, invasion and epithelial‑mesenchymal transition of oral squamous cell carcinoma

Abstract: Abstract. Annexin A1 (ANXA1) acts either as a tumor suppressor or an oncogene in different tumor types. Several clinical studies revealed that the expression of ANXA1 is associated with the pathologic differentiation grade in oral squamous cell carcinoma (OSCC) patients. However, the direct function of ANXA1 in OSCC progression has remained to be fully clarified. The present study was designed to investigate the role of ANXA1 in OSCC cell proliferation and invasion in vitro. Furthermore, whether ANXA1 was invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 32 publications
4
18
0
Order By: Relevance
“…Previous studies from our group 52 have already shown that the peptide induces cell proliferation in HUVECs, both under basal conditions and after stimulation by VEGF. Other studies using inflammation and tumor models evidenced that ANXA1 may stimulate proliferation and migration 53 or even inhibit proliferation 54 , most likely depending on the context of the experiment, cell type or tissue. Treatment of HUVECs with PL, alone or together with Ac 2-26 , also showed a low effect on cell viability.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies from our group 52 have already shown that the peptide induces cell proliferation in HUVECs, both under basal conditions and after stimulation by VEGF. Other studies using inflammation and tumor models evidenced that ANXA1 may stimulate proliferation and migration 53 or even inhibit proliferation 54 , most likely depending on the context of the experiment, cell type or tissue. Treatment of HUVECs with PL, alone or together with Ac 2-26 , also showed a low effect on cell viability.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the GO and KEGG were carried out. The result of our analysis showed that LGALS1, ANXA1, and ANXA2, which have an important roles in multiple tumors including clear cell renal cell carcinoma , pancreatic cancer , acute lymphoblastic leukemia , breast cancer , and oral squamous cell carcinoma , were significantly related to linc00152 gene expression ( P < 4.12 × 10 −60 ). Following this, we performed the GO and KEGG pathway analysis, and the results showed that linc00152 was significantly related to negative regulation of apoptotic processes.…”
Section: Discussionmentioning
confidence: 85%
“…ANXA1, a member of the annexins superfamily, is a structurally related calcium-dependent phospholipid-binding protein that has a core domain shared by the annexins superfamily and an N-terminal domain that is responsible for its unique function. It participates in important cell processes such as cell signaling, cell differentiation and apoptosis through regulating bubble aggregation, inflammatory response and the activity of phospholipase A2.More and more evidence shows that,ANXA1 affects cell proliferation, invasion, epithelial-mesenchymal transition [79][80][81][82] and chemoresistance. 39,83,84 ANXA1 is a substrate for protease C and tyrosinase, and possesses multiple calcium-phosphorus binding sites.…”
Section: Discussionmentioning
confidence: 99%